THE EFFECTIVENESS OF READING AND WRITING LITERACY ACTIVITIES IN IMPROVING UPPER GRADE STUDENTS’ READING AND WRITING SKILLS AT PRIMARY SCHOOL - Nandang Kosim (JMIE (Journal of Madrasah Ibtidaiyah Education), 2026)
This study examined the planning and implementation of reading-writing literacy activities and their effect on upper-grade students’ reading and writing skills at Irsyadul Ibad Integrated Islamic Elementary School, Pandeglang. A quasi-experimental design with a non-equivalent control group was employed, involving experimental and control groups selected without random assignment. Data were collected using classroom observation sheets and reading and writing skill tests. The observation results showed that the instructional planning and implementation were aligned with the principles and procedures of reading-writing literacy, including guided reading, text-based discussion, written response, and structured writing practice. The statistical analysis indicated a significant difference in students’ reading and writing skills, with a probability value of 0.001, which was lower than the significance level of 0.05. These findings demonstrate that reading-writing literacy activities had a significant effect on improving upper-grade students’ reading and writing skills. The study implies that systematically planned and consistently implemented reading-writing literacy activities can be used as an effective instructional strategy to strengthen literacy learning in elementary schools.